Cryosurgery for the treatment of pediatric plunging ranula: a conservative management - Moraes,Paulo de Camargo (2015)
Several methods of treatment for plunging ranulas have been described in the literature, such as: surgical treatment including the excision of the sublingual gland followed by transoral drainage of the pluging ranula, needle aspiration, excision of the ranula, cryosurgery and CO(2) laser excision. Marsupialization and micro-marsupialisation can be also recommended primarily to treat oral ranulas. The aim of this paper is to present the treatment of pediatric ranula with liquid nitrogen cryosurgery performed in a 8 year, 6-month-old male, without local anesthesia. We have outlined the current protocol of cryosurgery recommended in the management of ranulas, both clinical advantages and disadvantages, with emphasis on the clinical outcomes and also pediatric patients' safety. At the 1year follow-up visit, the lesion had disappeared completely. There was no recurrent lesion. Liquid nitrogen cryosurgery for management of ranulas may become a primary treatment modality prior to surgery in children.